Evaluation of tear film stability before and after laser in situ keratomileusis - Shrestha, GS; Wagh, S; Darak, A (Nepalese Journal of Ophthalmology, 2011)
DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5266 Nepal J Ophthalmol 2011; 3(2): 140-145